Modulation in Nutritional Quality of Microalgae, Chaetoceros calcitrans in Different Culture Media - K.P., Lincymol; Ittoop, Gijo; P., Lakshmi Devi; Joseph, Aneykutty (Fishery Technology, 2025)
The present study was initiated to identify the best medium for culture of Chaetoceros calcitrans that could provide better protein and lipid content while supporting good growth of the algae. The media selected were Walne’s, Miquel’s, Chu and f/2 media. The algae cultured in Walne’s, Miquel’s and f/2 media showed significantly higher content of lipid (P<0.05) in the late exponential phase. Protein content was the highest in Walne’s medium (32.53 ± 0.28% dry weight) as compared to other media tested. Maximum cell density was recorded in f/2 medium. Miquel’s medium gave the maximum carbohydrate content (16.92 ± 1.54% dry weight). It was observed that media could certainly influence the biochemical composition of microalgae and therefore selection of media should be based on the larval requirement of the target species. Results obtained in the present study revealed that microalgae cultured in Walne’s medium gave high values of protein and lipid content. Although cell count was the highest in f/2 medium, Walne’s medium provided the best nutritional quality of algae.